PENERAPAN MEDIA FILM SEBAGAI SUMBER BELAJAR UNTUK MENINGKATKAN KEMAMPUAN MENGOLAH INFORMASI SISWA DALAM PEMBELAJARAN SEJARAH - Lusiana Surya Widiani; Wawan Darmawan; Tarunasena Ma'mur (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
The background of this study is the lack of ability to process information of students in history subject in grade 11 Social I Pasundan 8 Senior High School Bandung. This can be seen from most students were only able to develop the ability to remember and memorize. When students are exposed to an issue, students were not able to process the information. The ability to process the information outlined in this study is the student’s ability to process information from a variety of sources of information when learning takes place. To that end, researchers are trying to do research with the goal of improving students’ ability to process information through the implementation of film media in history subject. This research is using a classroom action research methods design of Kemmis and Mc. Taggart. The classroom action research method (PTK) were done with four steps: planning, action, observation, and reflection. Based on the research that has been done, student progress in achieving the criteria on the indicator of the ability to process information that has been determined to experience a significant increase in each cycle. Through the implementation of film as media, the students used to process the information they receive. This shows that in the application of the film to enhance the students’ ability to process information is one way that can be used in the teaching of history in schools. The results of this study can be used as advice or recommendations as well as consideration for teachers so that students will have the ability to process information so that the teaching process become more meaningful.